Deep chronic microvascular white matter ischemic change as an independent predictor of acute brain infarction after thoracic aortic replacement. Issue 9 (2nd September 2018) - Obusez, Emmanuel C.; Svensson, Lars; Bullen, Jennifer; Obuchowski, Nancy; Jones, Stephen E.
Abstract: Background: Postoperative brain injury is a cause of mortality and morbidity in patients who undergo thoracic aortic replacement. Chronic microvascular white matter ischemic change (WMIC) has been shown to be associated with acute brain infarction in the general population. WMIC has also been shown to be an independent predictor of non‐focal neurocognitive changes, generalized seizures, and temporary neurologic dysfunction in patients who undergo thoracic aortic replacement. The aim of this study is to determine if WMIC is a risk factor for acute brain infarction in patients who undergo thoracic aortic replacement. Methods: A case‐control study of patients who underwent thoracic aortic replacement between 2001 and 2014 were reviewed for neurological changes after surgery and acute brain infarction on postoperative diffusion‐weighted imaging (DWI) magnetic resonance imaging (MRI). Patients with neurological changes were matched with control patients who underwent thoracic aortic replacement and had postoperative neurological symptoms without acute brain infarctions. Acute infarction was re‐assessed by reviewing DWI sequences on postoperative MRI. WMIC was assessed on FLAIR and T2WI sequences on both preoperative and postoperative MRI. Logistic regression was performed assessing the relationship of WMIC and acute ischemic infarction. Results: 5171 patients underwent thoracic aortic replacement; 179 had postoperative neurological changes, and of those 53 patients had acute brain infarction on postoperative DWI. Patients with deep WMIC were more likely to have acute DWI infarctions after thoracic aortic replacement ( P = 0.023). Conclusion: Our matched retrospective case‐controlled study shows deep WMIC to be a predictor of acute brain infarction on DWI after thoracic aortic replacement.